LITERASI DIGITAL DAN PEMBENTUKAN KESIAPAN ASN DIGITAL: PERAN MEDIASI PENERIMAAN TEKNOLOGI PADA MAHASISWA ADMINISTRASI PUBLIK - Nico Pranata Mulya; Nindi Riyan Gustin; Frans Dika Permana; Nida Silvia Lestari (Program Studi Ilmu Administrasi Negara, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Timor, 2026)
This study aims to examine the effect of digital literacy on digital readiness among prospective civil servants, with technology acceptance serving as a mediating variable. The sample consisted of 150 undergraduate students enrolled in the Public Administration program at Universitas Pamulang, Serang Campus. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0 software. The results indicate that digital literacy has a positive and significant effect on digital readiness among prospective civil servants (β = 0.346, p < 0.05). Digital literacy also significantly influences technology acceptance (β = 0.667, p < 0.05), while technology acceptance positively and significantly affects digital readiness (β = 0.423, p < 0.05). Mediation analysis reveals that technology acceptance partially mediates the relationship between digital literacy and digital readiness (β = 0.282, p < 0.05). The proposed model explains 49.4% of the variance in digital readiness. These findings contribute to the literature by integrating the Digital Competence Framework and the Technology Acceptance Model to explain individual-level digital readiness in the public sector context. Practically, the study provides insights for higher education institutions in designing curricula that strengthen digital competencies and foster positive attitudes toward technology to prepare graduates for digital government transformation.